A VALIDATED LC-MS/MS METHOD FOR PHARMACOKINETIC STUDY OF BRIVARACETAM IN HEALTHY RABBITS - Vasanth, D. Atul; Rajkamal, B. (International Journal of Pharmacy and Pharmaceutical Sciences, 2018)
Objective: A liquid chromatography-tandem mass spectrophotometric (LC–MS/MS) method was developed for quantification of brivaracetam in rabit plasma employing liquid-liquid extraction with ethyl acetate. Methods: Developed method was validated for specificity, precision, accuracy, recovery, and stability characteristics. Chromatographic separation was achieved on Chromolith C18column (100 mmx4.6 mmx5 µm) with 0.1% formic acid, adjusted to pH 3.2 as an isocratic mobile phase with a flow rate of 1.0 ml/min. the developed method was applied to assess pharmacokinetics parameters like Cmax, Tmax, t1/2 and AUC of brivaracetam in healthy rabbits. Results: The developed method was linear over the range of 0.16 to 8µg/ml. The regression equation for the analysis was Y=0.0053x+0.0018 with coefficient of correction (r2) = 0.998. The % mean recovery for brivaracetam was found to be between 95.7% to 106.5%. The mean intraday and inter-day precision of the method was found to be 0.77 to 3.72% for quality control standards. Brivaracetam showed Tmax of 1.025±0.061 and mean Cmax, AUC0®t andAUC0®a for Test formulation is 92.7±4.4, 496.21±26.4 and 504.20±30.68 respectively. Conclusion: A highly specific, rugged and rapid method with sufficiently low LLOQ was developed for analysis of routine samples of a single dose or multiple dose pharmacokinetic studies with any marketing formulation of brivaracetam.